FREQUENCY OF IPSILATERAL FEMORAL NECK FRACTURES IN PATIENTS WITH FEMORAL SHAFT FRACTURES - KHAN, B; TAREEN, NU; JUNAID, M (Biological and Clinical Sciences Research Journal, 2023)
Young people are regularly injured and get femoral shaft fractures. Comprehensive data is needed to determine the frequency of ipsilateral femoral neck fractures in people with femoral shaft fractures. In the present study, individuals with femoral shaft fractures will be examined to determine the frequency of ipsilateral femoral neck fractures. A retrospective study was conducted at the Department of Orthopedic Surgery, Combined Military Hospital (CMH) Rawalpindi, from January 2023 to August 2023. There were 160 participants in the research who had femoral shaft fractures. Preoperative radiographs and intraoperative results were examined to determine if the patients had ipsilateral femoral neck fractures. This retrospective study covered 160 femoral shaft fracture patients with averaged 35 years old, with 75% being male and 25% female. Road traffic accidents (62.5%), falls from height (25%) and sports injuries (3.75%) caused the greatest injuries. 8(5%) had ipsilateral femoral neck fractures. Patients with ipsilateral femoral neck fractures were 35 years old and were 75% male. 87.5% of patients had good surgical results, 6.3% fair, and 6.3% poor. The most frequent consequences were non-union (3.1%), malunion (1.3%), and infection (1.9%). This study identified 5% of ipsilateral femoral neck fractures in femoral shaft fracture patients. These patients must be carefully evaluated and managed to minimize missing or delayed identification of concomitant femoral neck fractures. There were 5% ipsilateral femoral neck fractures in femoral shaft fracture patients. These patients must be carefully evaluated and managed to minimize missing or delayed identification of concomitant femoral neck fractures. Early detection and treatment of these fractures may improve results and avoid complications.